Redundancy Category as a Means of Cognitive Foregrounding Mechanism - Igorevna, Filippova Olga (Researchparks Publishing, 2023)
The article discusses the issues of the theory of foregrounding in linguistic research, with special attention to the interpretation and terminological designation of this phenomenon by foreign and Uzbek linguists. The linguistic phenomenon of redundancy in a fiction text is analyzed not only as a necessary condition that ensures an adequate interpretation of information by the addressee, but also as a cognitive mechanism of foregrounding. Special attention is paid to the conceptual significance of redundancy means in the actualization of conceptual meanings that are significant for the interpretation of a literary text. The thesis that redundancy is a cognitive principle of information distribution in a fiction text is substantiated.